2014
DOI: 10.1093/infdis/jiu264
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Malaria Prevalence and Its Potential Consequences for Immunity in Pregnant Women

Abstract: The impact of falling parasite prevalence on anti-Plasmodium falciparum serological indicators in pregnant women varies by setting. Increased ITN coverage may affect development of antibodies to recombinant antigens, but levels of opsonizing IgG remained stable over time. Opsonizing IgG against placental-binding IEs may persist, thus offering longer-lasting protection against malaria during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 43 publications
5
30
0
1
Order By: Relevance
“…The concentrations of both antibodies showed a decline with IPTp uptake probably as a result of decay in antibodies or as a result of the clearance of parasitaemia by treatment with SP. This is consistent with other studies [43, 48, 55, 56], which also found a decline in the levels of antibodies against several antigens during pregnancy and after delivery. The decrease in antibody levels is believed to be linked with pregnancy-specific malaria immunity rather than to non-pregnancy associated malaria antigens [48] as speculated elsewhere [50] or possibly to short-lived responses in the absence of infection [43, 55].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The concentrations of both antibodies showed a decline with IPTp uptake probably as a result of decay in antibodies or as a result of the clearance of parasitaemia by treatment with SP. This is consistent with other studies [43, 48, 55, 56], which also found a decline in the levels of antibodies against several antigens during pregnancy and after delivery. The decrease in antibody levels is believed to be linked with pregnancy-specific malaria immunity rather than to non-pregnancy associated malaria antigens [48] as speculated elsewhere [50] or possibly to short-lived responses in the absence of infection [43, 55].…”
Section: Discussionsupporting
confidence: 93%
“…Regardless of these benefits, there is concern that “any exposure-reducing interventions could result in the loss of or failure to acquire protective (PAM) immunity” [4143] which would increase the overall, long-term disease burden [44] by increasing morbidity and mortality [45, 46]. The use of IPTp with Sulfadoxine–pyrimethamine (SP) treatment of primigravidae has also been shown to reduce levels of plasma IgG, which protects against pregnancy-associated falciparum malaria [47, 48] and severe malaria among children [49]. However, the extent to which IPTp may interfere with acquisition of protective immunity against PAM is largely undefined, particularly in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…As well as having pharmacokinetic determinants, the duration of protection will depend on the degree of malarial immunity. Where there has been a reduction in exposure to malaria through strategies, including ITNs (including PNG), immunity may decline as a result (60), and pregnant women may therefore have a shorter period of protection after the same DHA-PQ dose. There is a clear need for monitoring the incidence of malaria in pregnancy where IPTp is used, as part of in vitro and other in vivo measures of local parasite resistance.…”
Section: Discussionmentioning
confidence: 99%
“…, see [20; 36; 74; 81; 82; 83; 84; 85; 86; 87; 88]). Because the parasite is threatened by the immune system, it has evolved escape strategies, including the intriguing use of antigenic variation mechanisms [89; 90; 91].…”
Section: Malaria As the Paradigm Infectious Diseasementioning
confidence: 99%